(untitled) (Journal of Fatima Jinnah Medical University, 2026)
Background: Multilevel cervical myelopathy (MCM) is a progressive neurological disorder caused by spinal cord compression. Posterior decompressive procedures such as laminoplasty and skip laminectomy are commonly employed, but their comparative outcomes remain unclear, particularly in regional populations. This study compared postoperative outcomes of skip laminectomy and laminoplasty. Methods: This randomized controlled trial was conducted at Sir Ganga Ram Hospital from March 2023 to March 2024. Forty-eight patients aged 35–65 years with MRI-confirmed multilevel cervical spondylotic myelopathy (≥3 levels) were enrolled and randomized using computer-generated allocation into skip laminectomy (n=24) or open-door laminoplasty (n = 24). Patients with kyphosis, ≤2 involved levels, prior cervical surgery, trauma, infection, or need for fixation were excluded. Primary variables included operative time, intraoperative blood loss, cervical range of motion, pain (VAS), and neurological status (Nurick grade). Outcomes were assessed preoperatively, at 3, and 6 months. Neurological improvement was defined as a ≥1-grade reduction in Nurick score. Operative time was recorded from incision to closure, and blood loss was calculated as suction volume after subtracting irrigation volume. Data were analyzed using SPSS v24.0, with p-value <0.05 considered statistically significant. Results: Mean age was comparable between groups (skip laminectomy: 50.67; laminoplasty: 49.13; p-value >0.05). Operative time was significantly shorter in the skip laminectomy group compared with laminoplasty (97.08 ± 31.05 vs. 127.42 ± 34.73 minutes; p-value = 0.03). Intraoperative blood loss was also significantly lower in the skip laminectomy group (75.79 ± 2.23 vs. 282.63 ± 1.27 mL; p-value <0.001). No significant differences were observed in Nurick grade, pain, or cervical range of motion at baseline, at 3 months, or at 6 months of follow-up (p-value >0.05). Conclusion: Both procedures produced comparable neurological, pain, and functional outcomes in MCM; however, skip laminectomy demonstrated superior intraoperative efficiency with reduced operative time and blood loss.